Variations in the use of personal pronoun agreement in Acehnese: A sociolinguistic approach - Armia, Armia; Iskandar, Denni; Zuriana, Cut; Nurrahmah, Nurrahmah (Studies in English Language and Education, 2023)
This study aims to identify variations in the use of personal pronoun agreements in the Acehnese language based on a sociolinguistic approach, by focusing on the North Aceh dialect. A descriptive-qualitative method was used and data were collected through interviews. These interviews were recorded, transcribed, and analyzed using the sociolinguistic approach by structure and semantics. The results of the study showed that the personal pronouns of the Acehnese language are influenced by social factors such as age, social status, and familiarity. In the context of the age factor, there are variations in the use of personal pronoun agreements related to communication patterns between the younger and older generations. In social interactions with differences in social status, the use of personal pronoun agreements that reflect respect and recognition of social status is more dominant. Meanwhile, in familiarity, the use of more formal or informal personal pronouns depends on the degree of familiarity between the speakers. Overall, variations in the use of agreement personal pronouns in the Acehnese language are influenced by sociolinguistic factors that reflect social dynamics, cultural norms, and relationships between individuals. Understanding these variations can provide better insight into social interactions, social hierarchies, and familiarity norms in Acehnese society.